Bibliografía - Quiles, Ismael; Felipe, McGregor; García, Luis Adolfo (Fascículos de la Biblioteca, 1942)
Presenta una reseña de los siguientes libros:-Wilhel Wildenband. Historia de la filosofía. Tomo 3. México: Antigua Librería Robredo, 1942.-W. Farrell. A companion of the Summa. II: The persuit of happiness. London: Sheed & Ward, 1939.-Cicerón, Los oficios. Traducción de Manuel Valbuena. Buenos Aires; México: Espasa-Calpe, 1943.-Studies in comparative religion. General editor: rev. E. C. Messenger, Ph. D. London. Catholic Truth Society. 5 tomos.-Henry Davis. Moral and pastoral theology. London: Sheed and Ward, 1941. 4 tomos.-The most rev. Alban Goodier. Archbischop of Hierapolis. An introduction to the study of ascetical and mystical theology. London: Burns Oates, 1939.-Alban Goodier. The public life orur Lord. London: Burns Oates, 1941.-Michael Torres. Brevis cursus sacrae scripturae ad Semirarii alumnorum utilitatem. Apud Seminarum de Guadalupe, Archidiocesis Sanctae Fidei, 1942.